Business Activity in Mosque According to Maliki and Shafi'i Fiqh: A Case Study of Masjid Taqwa Al-Qulaib Muhammadiyah Medan Estate - Rambe, Pormasi; Lubis, Zulpahmi (Jayapangus Press, 2024)
Trading has been a long-standing activity, dating back to the time of the Prophet Muhammad. It is defined as a form of work that encompasses activities such as buying and selling, renting, pawning, cooperation (mudharabah or musyarakah), representation, and more, with the exception of activities that are expressly forbidden, such as causing harm, deception, gambling, and usury. This study aimed to ascertain the perspectives of Fiqh Maliki and Shafi'i on the transactions carried out within the mosque. Then, to Next, the study aims to identify the most pertinent viewpoint on the business activities within the mosque, as per the Fiqh of Maliki and Shafi'i. arch method is based on field research, the data needed in the community, and emphasizes the results of data collection from informants. Therefore, this study employs a descriptive-qualitative approach, gathering descriptive data in the form of written or oral words (speech) from informants chosen by the researcher to carry out the activities in the mosque setting. efer to this study as empirical research, as it seeks to uncover theories about the legal process and its influence on society. The result of this research Maliki Fiqh permits business activities on the terrace of the Taqwa Muhammadiyah Medan Estate mosque, as it is outside the prayer area, while Shafi'i Fiqh opposes such activities, arguing they disrupt worship and compromise the mosque's sanctity.